Hiding from the climate: Characterizing microrefugia for boreal forest understory species. (12th December 2019) - Greiser, Caroline; Ehrlén, Johan; Meineri, Eric; Hylander, Kristoffer
Abstract: Climate warming is likely to shift the range margins of species poleward, but fine‐scale temperature differences near the ground (microclimates) may modify these range shifts. For example, cold‐adapted species may survive in microrefugia when the climate gets warmer. However, it is still largely unknown to what extent cold microclimates govern the local persistence of populations at their warm range margin. We located 99 microrefugia, defined as sites with edge populations of 12 widespread boreal forest understory species (vascular plants, mosses, liverworts and lichens) in an area of ca. 24, 000 km 2 along the species' southern range margin in central Sweden. Within each population, a logger measured temperature eight times per day during one full year. Using univariate and multivariate analyses, we examined the differences of the populations' microclimates with the mean and range of microclimates in the landscape, and identified the typical climate, vegetation and topographic features of these habitats. Comparison sites were drawn from another logger data set ( n = 110), and from high‐resolution microclimate maps. The microrefugia were mainly places characterized by lower summer and autumn maximum temperatures, late snow melt dates and high climate stability. Microrefugia also had higher forest basal area and lower solar radiation in spring and autumn than the landscape average. Although there were common trends across northern species in how microrefugia differed from the landscape average, there were also interspecific differences and some species contributed more than others to the overall results. Our findings provide biologically meaningful criteria to locate and spatially predict potential climate microrefugia in the boreal forest. This opens up the opportunity to protect valuable sites, and adapt forest management, for example, by keeping old‐growth forests at topographically shaded sites. These measures may help to mitigate the loss of genetic and species diversity caused by rear‐edge contractions in a warmer climate. Abstract : Sites hosting rear‐edge populations (microrefugia) were mainly places characterized by lower summer and autumn maximum temperatures, late snow melt dates and high climate stability. These places were often topographically shaded and/or densely forested. Our findings provide biologically meaningful criteria to locate and spatially predict potential climate microrefugia in the boreal forest.